The Influence Of Professional Ethics, Professional Skepticism, And Auditor Competence On Auditor Quality Moderated By Auditor Experience - Rommel Togatorop (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the influence of Profesional ethics, Profesional skepticism, and auditor competence on auditor quality with auditor experience as a moderating variable. Auditor quality is seen as an important indicator in measuring the quality of audits that provide trustworthy integrity of financial report information. This research uses questionnaire data from auditors in DKI Jakarta, during the period of the writing. The Partial Least Squares (PLS) analysis method is used to test the relationships between the variables under study. The results of this research are expected to provide valuable insights into how Profesional ethics, Profesional skepticism, and auditor competence influence auditor quality, as well as how auditor experience can moderate the relationships between these variables. The implications of this research are expected to assist management decision-making in determining the Public Accounting Firm to carry out audit assignments so that the resulting audited financial reports can be trusted for their integrity.